Os cafés da baixa do Porto. Materialidade, uso e significado do espaço construído - Ana Ilina Salgado de Almeida (2013)
A built space tells stories in specific times of its existence. In itsconstruction and physical qualities, this space is influenced by a vasterspatial context, with a sociocultural nature particular to a certain time period.Once built, its spatial dimension gives rise to life experiences, socialcontacts, communications, conveying of ideas; space becomes a nucleus ofspecific socioculturality, which in turn reflects itself on the very (re)definitionof the surrounding environment. This thesis aims at understandingspace taking as reference the relations that are established between its materialityand the extra adjoining material dimensions that it encompasses,and how these relations can be found within a particular context.By analyzing coffee shops (and similar premises used for the saleand consumption of drinks) located in Oporto's downtown (a territory thatmore continuously has preserved the presence of these spaces since theyemerged in the city) that by their recreational nature (allowing informaland less rigid continuities, and thus more authentic in translating ways ofbeing and communicating), by their semipublic nature (providing both avast and assorted absorption of publics and its observation and analysis ina controlled way), and by their undeniable bond with cultural trends andmutations), the final aim is to understand how spaces are built in order totry to address specific needs of particular sociocultural environments andgroups, and how―once built―they answer them (which life experiencesand sociocultural exchanges are indeed processed within them), and therelevance of their role in (re)defining a territory or a culture.After understanding the territory under study, followed by an approachon the importance of usage in architecture (a concept that comprisesthe general modes of interaction between man, sociocultural contextand the space in which he lives), there follows an empirical study based onthe gathering of information, firstly at the territorial scale and then, morespecifically, of the coffee shops spaces and their physical nature and humanambience. This information is then systematized and comparativelyanalyzed in order to understand the relations between the diverse 'coffeeshops' and the territory and among themselves, and also to try to understandhow do materialities connect themselves with the human dimensions, andwhat role do these sociocultural 'containers' play in (re)structuring theirenvironment